VERBAL, SOCIAL AND BIOGENETIC CODES OF EMOTION EXTERNALIZATION: AN AFFECTIVE-DISCURSIVE ACCOUNT - Iryna P. Pinich (Alfred Nobel University Journal of Philology, 2022)
The article elucidates modern trends in humanities and social studies to encompass affective corporeality in the emotional conceptual sphere of the person, the structure of her social identity, and into processes of communal sense-making. But despite the prominence of the turn to affectivity which is putatively at the core of many social processes, discourse must be equally addressed to outline the epistemic role of emotional experiences. Therefore, the goal of the paper is to highlight the need for integrating the findings of both discourse and affect studies which will significantly benefit emotiology in unveiling the processes of social construction of reality. To meet the goal the following objectives are set: 1) to outline the semiotic nature and pragmatic potential of affect somatic concomitants; 2) to analyze the unity of social and biogenetic codes of affect and emotion externalization; 3) to provide an overarching classification of verbal means for affect and emotion manifestation; 4) to highlight the role of cognized corporeality of emotions; 5) to present the prospects of an integral approach to the study of affective-discursive sense-making. The methodology of the study involves general-scientific methods of analysis, synthesis, comparing, and deduction. Results. Current emotion theories in linguistics, philosophy, and psychology exhibit a general tendency towards the integration of embodied emotional and sensual experience in epistemic and sense-making practices of social interaction. An emotional pool proves indispensable from the pool of knowledge and involves shared experience of affective and emotional responses, their conventionalized and sedimented externalization, the library of verbal and nonverbal means of their manifestation, regulation, negotiation, and channeling. Consequently, the unison of scholarly claims resides in the recognition of both biological and social aspects of affectivity, verbal expression and/or representation of which elicits recognition and an embodied response in the co-emoter. The commonality of affective interaction is claimed formative in constructing worldviews and beliefs. Therefore, the pragmatic potential of verbal and nonverbal affectivediscursive practices favours efficient social affiliation and communal construction of reality simultaneously setting social boundaries within a society. Recurring and reproducing scenarios of affective interaction are based on the system of conventional behavioural and linguistic signs which foster meaning-making practices. The library of somatic signs can be accessed via biogenetic modality, modality on trigger, and modality on learning. This code is grounded in innate physiological responses and unequivocally relates to corresponding situations through stereotypical behavioral patterns. Modality on learning bridges biogenetic and alphabetic codes as the nativism of both anchors semantic correlation, with the difference that the latter system of signs is adopted only conventionally. A discursive account of emotional interaction has resulted in an integral classification of verbal means for affect and emotion externalization that equally involve verbal and nonverbal modes. Emotion triggers, emotional situations, psycho-physiological experiences, state and action tendencies are included in the comprehensive inventory of language means for emotion manifestation. Expressive and descriptive methods can also serve as means of invoking emotional response in other social members in the form of embodied simulations. This is engendered by the process of emotion knowledge acquisition which occurs both through embodiment and narrative practices. The knowledge of social and cultural aspects of one’s emotional stance involves a multilateral account of subjective experience shared by other members of a culture. Thus, emotional alignment is achieved in social acts through manifold resources of language that proves affective-discursive practices defining in sense-making and the approach seminal in further studies of social processes.